In situ photogenerated hydroxyl radicals in the reaction atmosphere for the accelerated crystallization of solution-processed functional metal oxide thin films. Issue 7 (16th January 2023) - Gómez-Lopez, Alicia; Rivas, Y. Andrea; López-Fajardo, Sergio; Jiménez, Ricardo; Ricote, Jesús; Pecharromán, Carlos; Montero, Isabel; Bretos, Iñigo; Calzada, M. Lourdes
Abstract : We propose a disruptive method to accelerate the crystallization at low temperatures of functional metal oxide films whereby hydroxyl radicals (OH) are photogenerated in situ from the atmosphere where solution-deposited layers are UV-irradiated. Abstract : We propose a disruptive method to process metal oxide thin films whereby hydroxyl radicals (˙OH) are photogenerated in situ from the atmosphere where the corresponding solution-deposited layers are UV-irradiated. The reaction of these radicals with the film results in the transformation of the deposited layer into a highly-densified amorphous metal–oxygen network that easily evolves to the crystalline film at much lower temperatures than those traditionally used (over 600 °C). An exhaustive study has allowed us to determine the underlying mechanisms involved in the accelerated crystallization of these oxides by the presence of ˙OH radicals during the process. We demonstrate that the method is applicable to all-solution metal oxide thin films, validating its general application in thin films of the binary Bi2 O3 oxide and of more complex oxides like BiFeO3 and Pb(Zr0.30 Ti0.70 )O3 ferroelectric perovskites. It is shown that the metal oxide crystallization occurs between 250 °C and 350 °C, a temperature range hundreds of degrees below their conventional processing temperatures and fully compatible with their direct growth on flexible polymer substrates. This processing method opens new opportunities for the integration of high-performance multifunctional oxide layers into the next-generation devices demanded today by emerging technologies such as flexible or wearable electronics.